Safety Culture Among Car Drivers and Motorcycle Riders in Norway and Greece: Examining the Influence of Nationality, Region, and Transport Mode - Nævestad, Tor-Olav; Laiou, Alexandra; Yannis, George (Frontiers in Sustainable Cities, 2020)
The aims of the study are to: 1) Compare road safety behaviours among car drivers and motorcyclists in five different regions in Norway and Greece, 2) Examine the factors influencing road safety behaviours in these groups, and 3) Examine the relationship between road safety behaviours and accident involvement. The study is based on survey answers from car drivers and motorcycle riders in two Greek and three Norwegian regions (N=1212). RSC is defined as shared patterns of behaviour and shared expectations to other road users. Results indicate shared national RSC among Norwegian riders and drivers in the three Norwegian regions. Results from the Greek sample indicate the importance of the regional level for RSC, and a unique RSC on the studied Greek Island. The data does not indicate that transport mode is important for road safety behaviours or RSC. Our analyses indicate that RSC is important, as it is closely related to road safety behaviours, which in turn is related to accident involvement. This suggests that accidents may be reduced by influencing RSC. To contribute to such efforts, we discuss how and where RSC is created and how it influences road safety behaviour, based on our results.